Fifty Years of Research on Vedas: A Bibliometric Analysis - Ahuja, Deeksha; Madan, Pankaj (Prabandhan: Indian Journal of Management, 2022)
Vedas are gaining a lot of popularity over the world. According to the Scopus database, Vedic research has increased since 2010. However, there has been no bibliometric study on Vedas. Some individuals are inquisitive about how the Vedas may aid in domains such as humanities, arts, computer science, social science, and management, and there are noteworthy differences in the attention this subject has received among the writers. Others are concerned about the ongoing search for potential cures for numerous ailments and the production of missiles. The authors used the Scopus dataset to perform a bibliometric review of Vedic studies from 1970 to 2020 to determine the current trend in Vedic publications. Using Microsoft Excel for descriptive analysis, the annual trend of publishing, top nations of research, and top subjects were investigated. While utilizing VOSviewer software for visual analysis of the data, we looked at the co-occurrence of all keywords, author co-citation, reference co-citation, and journal co-citation analysis. The study concludes that the number of Vedic publications has grown in the last 10 years. We observed 21 nations and regions that are interested in Vedic research. India has a far higher number of publications than the United States and other countries in the Vedas. Arts and humanities, medicine, and engineering are the major fields of research in Vedas, followed by social sciences.